2019
DOI: 10.1029/2019ja027360
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Very Short Period Atmospheric Gravity Waves in the Lower Ionosphere Using Very Low Frequency Waves

Abstract: We present observations of very short period (<5 min) wavy fluctuations (WFs) in the lower ionosphere (75-85 km) on the night of 21 January 2016, using subionospherically propagating very low frequency signals. Four out of six transmitter signals recorded by the very low frequency/low frequency receiver at the Pisgah Astronomical Research Institute showed WFs simultaneously. However, their time of occurrence and intensities were different. Power spectral analysis indicates a period of~3-4 mins, largely associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…They found that the TIDs are most likely induced by secondary gravity waves from local horizontal body forces created by the dissipation of primary gravity waves from deep convection. These findings have also been confirmed by other studies (Liu et al., 2021; Maurya et al., 2019; Miyoshi et al., 2018; Snively & Pasko, 2008; Vadas & Becker, 2018; Zhao et al., 2020). To date, the effects of convective activity on the ionosphere have various explanations.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…They found that the TIDs are most likely induced by secondary gravity waves from local horizontal body forces created by the dissipation of primary gravity waves from deep convection. These findings have also been confirmed by other studies (Liu et al., 2021; Maurya et al., 2019; Miyoshi et al., 2018; Snively & Pasko, 2008; Vadas & Becker, 2018; Zhao et al., 2020). To date, the effects of convective activity on the ionosphere have various explanations.…”
Section: Introductionsupporting
confidence: 84%
“…In Figures 5 and 6, short‐period ionospheric disturbances were mainly concentrated from May to August and reached their maxima around May and June, which occurred mainly around midnight. According to previous studies that focused on gravity waves, gravity waves tend to propagate in the opposite direction to that of background winds as a result of wind‐filtering effects (Lindzen, 1981; Maurya et al., 2019; Nishioka et al., 2013). In summer, as shown in Figures 8c–8f, the zonal wind fields above the troposphere were dominated by westward winds, and the whole meridional wind fields were relatively weak.…”
Section: Resultsmentioning
confidence: 99%
“…The winds are converging from south and north of the Chile region and they strengthened with magnitudes of about 60 m/s to the east. As suggested in previous works 28 30 the AGWs can easily pass through the critical levels when they propagate opposite to wind direction. It means that background wind direction during eclipse time supports the AGWs propagation towards northward and opposes southward.…”
Section: Discussionsupporting
confidence: 54%
“…The wind data is used from the European Centre for Medium-Range Weather Forecasts (ECMWF) Reanalysis 5 product ECMWF 26 . The data are produced in 137 hybrid sigma pressure levels covering the surface to ~ 80 km altitude, with a spatial resolution of ~ 31 km 27 , which can be As suggested in previous works [28][29][30] the AGWs can easily pass through the critical levels when they propagate opposite to wind direction. It means that background wind direction during eclipse time supports the AGWs propagation towards northward and opposes southward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation